2021
DOI: 10.3389/fpsyg.2021.689058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Mental Well-Being, Exercise Routines, and the Intake of Image and Performance Enhancing Drugs During the Coronavirus Disease 2019 Pandemic: A Comparison Across Sport Disciplines

Abstract: Introduction: Physical distancing under the coronavirus disease 2019 (COVID-19) pandemic had a significant impact on lifestyles, including exercise routines. In this study, we examined the relationship between mental health and addictive behaviors, such as excessive exercise and the use of image and performance enhancing drugs (IPEDs) across 12 sport disciplines.Materials and methods: A large cross-sectional sample of the adult population (N = 2,295) was surveyed. The mean age was 33.09 (SD = 11.40). The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A systematic review concluded that the efficacy of Baduanjin exercise in reducing depression and anxiety symptoms in people with physical or mental illnesses [ 73 ]. In addition, some studies have shown that excessive exercise or exercise addiction harms anxiety and psychological well-being [ 74 ]. Simultaneously, during the pandemic, people who exercise more are less anxious than people who exercise less [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review concluded that the efficacy of Baduanjin exercise in reducing depression and anxiety symptoms in people with physical or mental illnesses [ 73 ]. In addition, some studies have shown that excessive exercise or exercise addiction harms anxiety and psychological well-being [ 74 ]. Simultaneously, during the pandemic, people who exercise more are less anxious than people who exercise less [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data were stored in a secure platform at the University of Hertfordshire. Conventional data from this study sample (including IPEDs use/body image/exercise habits) were reported previously [ 9 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the pandemic has constituted a unique opportunity to analyse social behaviours, including with respect to social media. Perceived reliance on social platforms may unveil or enhance dysfunctional mechanisms, especially ones correlated to body image and social acceptance, like appearance anxiety, excessive exercise, eating habits, and usage of supplements to improve either physical activity or body shape [130,135]. Concurrently, mechanisms related to social comparison may lead to repeated checking on others' contents, especially those recognized as most leading and inspiring, investing longer time on active social media activities, like posting, commenting, and sharing content, and passive ones like scrolling and browsing profiles.…”
Section: Social Factors and Puimentioning
confidence: 99%